Application of High Level Programming Language (Visual Basic): A Review (Journal of Science and Technology, 2020)
:Visual Basic is a one type of high-level Object Oriented Programming Language. It is developed by the Microsoft.NET Framework. It has finally become a fully-generated Object Oriented Programming Language with all the associated features one would come to expect. It allows programmers to handle much larger applications, through improved scalability and reusability with all features than any other programming language. Various VB Tools are used in this program. This article discusses the new features using .Net code examples to real applications in Computer Technology.